(untitled) (Jurnal Elektronika dan Telekomunikasi, 2022)
Sustainable future development relies on solar radiation, which is the main source of renewable energy. Thus, in this article, the monthly average global solar irradiation of four sites in the Sudanian zone region of Chad is estimated using different empirical models. The data used in this study were collected at the General Directorate of Meteorology of Chad. The reliability and accuracy of six models estimating global solar radiation were validated and compared by statistical indicators identifying the most accurate model. The results obtained show that the Allen model has the best performance for the Moundou site (5.760 kWh/m²/d, R2=0.843), the Angstrom Prescott model for the Sarh sites (5.658 kWh/m²/d, R2=0.805) and Pala (5.793 kWh/m²/d, R²=0.889), the Sabbagh model for the Bongor site (5.657 kWh/m²/d, R²=0.888). These models are validated against NASA data. The results show that the Sudanian zone of Chad has good solar potential and is therefore suitable for possible exploitation.